2023
DOI: 10.1002/jmv.28705
|View full text |Cite
|
Sign up to set email alerts
|

Clinical performance of a newly developed domestic urine‐based HPV test for cervical cancer screening in China

Abstract: Although urine-based human papillomavirus (HPV) detection is promising in cervical cancer screening, it has not yet been well-developed. Women aged 30-65 were invited to participate in the current study to provide one urine and two paired vaginal samples. Urine was detected by polymerase chain reaction (PCR)-based HPV test (urine-based HPV test). Two vaginal samples were tested by careHPV and GenPlex ® HPV genotyping assay, respectively. Women with vaginal HPV positive were called back for colposcopy and biops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Currently, there is a growing body of research focused on the use of urine as a medium for detecting HPV DNA, with several studies either underway or already commercialized. 25 , 26 , 27 , 28 , 29 , 30 While urine has been found to yield similar results to self‐collected vaginal specimens, some investigations have indicated that urine may be less sensitive than vaginal samples. 31 This discrepancy has been attributed to the lower concentration of HPV DNA in urine compared to cervical samples, necessitating the development of a highly sensitive detection method to ensure ample HPV DNA detection.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is a growing body of research focused on the use of urine as a medium for detecting HPV DNA, with several studies either underway or already commercialized. 25 , 26 , 27 , 28 , 29 , 30 While urine has been found to yield similar results to self‐collected vaginal specimens, some investigations have indicated that urine may be less sensitive than vaginal samples. 31 This discrepancy has been attributed to the lower concentration of HPV DNA in urine compared to cervical samples, necessitating the development of a highly sensitive detection method to ensure ample HPV DNA detection.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al reported a newly developed urine‐based HPV test 10 . Their work demonstrates the enthusiastic efforts of researchers and clinicians to investigate and optimize the performance of urine‐based HPV screening.…”
Section: Immediate Need For Validated Kits For Hpv Detection Based On...mentioning
confidence: 99%
“…For this purpose, a framework for validating HPV tests on self-samples, including urine, has been published to simplify the comparison of study results and the subsequent translation of these tests to clinical practice 9. This will give real insight on the performance of HPV detection in urine, reduce the observed variability and allow its implementation in clinical practice.Xu et al reported a newly developed urine-based HPV test 10. Their work demonstrates the enthusiastic efforts of researchers and clinicians to investigate and optimize the performance of urine-based HPV screening.…”
mentioning
confidence: 99%